Targeting Ischemia Reperfusion in Intestinal Transplantation by COX-2 Inhibition—A S.M.A.R.T Approach?. Issue 11 (November 2016) - Pascher, Andreas
Abstract : Dr. Pascher discusses the findings of Schildberg et al that COX-2 inhibitors ameliorate ischemia/reperfusion injury in orthotopic rat intestinal transplant in the context of a clinical scenario: is the therapy SMART:its Specific/Significant, Measurable/Manageable, Achievable/Appropriate, Realistic/Relevant, and Time-appropriate?